The masculinization of the feminine language in Peruvian films and monologues - Gutiérrez Luyo, Alexis Fernando (2019)
The masculinization of the feminine language is an issue with little research. The main objective of this paper is to explain the phenomenon of masculinization that occurs in the language of women in Peru, recreated in spaces such as cinemas and monologues. From a methodological point of view, we examine the use of  masculinized words and phrases proffered by women in two films and two monologues (stand up comedy). The paper concludes that masculinized speech responds to the performance of the subject in relation to certain situational and social contexts.